1961
DOI: 10.1136/jech.15.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Habits of Young Soldiers

Abstract: Broadly speaking there are in the Army three categories of young soldier-the Apprentice Tradesman, the Junior Leader, and the Band Boy. The 84 copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
3
9
0
1
Order By: Relevance
“…Our results therefore suggest that the increased risk of COPD in older veterans is a consequence of the high rates of smoking by serving military personnel, especially in the 1960s and 1970s, which have been reported in a number of earlier studies 5 6 25. The results are also consistent with the increased risk of lung cancer and smoking-related cancer in older and shorter-serving veterans (especially if ESL), compared with non-veterans, which we have found in the Scottish Veterans Health Study,26 and with the increased risk of acute myocardial infarction in the same population which we attributed to higher rates of smoking 8.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our results therefore suggest that the increased risk of COPD in older veterans is a consequence of the high rates of smoking by serving military personnel, especially in the 1960s and 1970s, which have been reported in a number of earlier studies 5 6 25. The results are also consistent with the increased risk of lung cancer and smoking-related cancer in older and shorter-serving veterans (especially if ESL), compared with non-veterans, which we have found in the Scottish Veterans Health Study,26 and with the increased risk of acute myocardial infarction in the same population which we attributed to higher rates of smoking 8.…”
Section: Discussionsupporting
confidence: 60%
“…Although formal records of Defence-wide military smoking cessation policy have not been located prior to 2001,20 Richards and Crowdy record that as early as 1962, ‘ The Army Medical Services have recently started a programme of health education on smoking ’, which provided the justification for their 12-year prospective study to examine changes in smoking prevalence in soldiers in the Army's junior units, in which school-leavers served in an educational and training capacity, from age 15 to 18 years, prior to moving into adult service 6. The results of the follow-up study provide an insight into the effectiveness of this early military health-promotion initiative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1959, Richards and Crowdy (1) found that the smoking habits of young soldiers joining the Army were similar to those of school children of the same age. More than 50% of the 15-year old entrants had started smoking before they joined the Army.…”
Section: Introductionmentioning
confidence: 97%
“…Although there are no confirmed statistics relating to smoking prevalence among soldiers in the British Army prior to 1959,11 there is some credibility attached to a figure of 96.5% based on the deliberations of the Princess Mary's Gift Fund, a fund inaugurated by Princess Mary in October 1914 which aimed to provide a Christmas gift for every serviceman at the front or at sea. The gift consisted of a brass box that contained tobacco, cigarettes, a pipe and lighter.…”
mentioning
confidence: 99%